Effect of compiling LEGO Play on sensory and motor skills in Toddlers - Eqlima Elfira; Bina Melvia Girsang; Indrawati (International Journal of Education and Humanities, 2021)
Toddlers have behavioral styles or temperaments that affect sensory and motor interactions. This research effectively deals with children's emotions in providing education by honing their fine and gross motor skills. The research aimed to determine the effect of composing lego on the sensory and motor skills of toddlers. The method in this research is pre-experiment with one intervention group on 10 toddlers. This study used a questionnaire and observation for 2 months given with playing techniques in the open. Of the 10 toddlers, Eight toddlers were found to have creativity in arranging legos according to their imagination, and two toddlers helped the process of compiling legos with happiness and enjoyment. Lego not only trains sensory and motor skills but helps develop toddlers' creativity